Review of the braconid parasitoid subfamily Doryctinae (Hymenoptera, Braconidae) from the United Arab Emirates and Yemen - Belokobylskij, Sergey A.; van Achterberg, Cornelis (European Journal of Taxonomy, 2021)
Yemen is provided for the first time. The following genera are recorded in the southern Arabian Peninsula for the first time: tribe Doryctini – Hemispathius Belokobylskij & Quicke, 2000 and Doryctes Haliday, 1836; tribe Spathiini – Parana Nixon, 1941 and Spathius Nees, 1819; tribe Hecabolini – Hemidoryctes Belokobylskij, 1992 and Parallorhogas Marsh, 1993; tribe Heterospilini – Heterospilus Haliday 1936; tribe Rhaconotini – Platyspathius Viereck, 1911 and Rhaconotinus Hedqvist, 1965. Sixteen species and one subspecies are described as new for science: Dendrosotinus (Gildoria) maculipennis Belokobylskij sp. nov., D. (G.) subelongatus Belokobylskij sp. nov., Doryctes (Neodoryctes) arrujumi Belokobylskij sp. nov., Parana arabica Belokobylskij sp. nov., Spathius alkadanus Belokobylskij sp. nov., S. austroarabicus Belokobylskij sp. nov., S. lahji Belokobylskij sp. nov., S. subafricanus Belokobylskij sp. nov., Hecabalodes maculatus Belokobylskij sp. nov., Platyspathius (Platyspathius) longicaudis Belokobylskij sp. nov., P. (P.) brevis Belokobylskij sp. nov., Rhaconotinus albosetosus Belokobylskij sp. nov., Rhaconotus brevicellularis Belokobylskij sp. nov., Rh. magniareolus Belokobylskij sp. nov., Rh. microexcavatus Belokobylskij sp. nov., Rh. vanharteni Belokobylskij sp. nov. and Hemidoryctes carbonarius postfurcalis Belokobylskij subsp. nov. Two new generic combinations are proposed: Hemispathius pilosus (Granger, 1949) comb. nov. (transferred from Doryctes) and Parallorhogas testaceus (Szépligeti, 1914) comb. nov. (transferred from Opius). Rhaconotus decaryi Granger, 1949 is here synonymised with Rh. menippus Nixon, 1939 (syn. nov.). A lectotype for Doryctes pilosus Granger, 1949 is designated. The following species are recorded for the UAE and/or Yemen for the first time: Dendrosotinus ferrugineus (Marshall, 1888), Hemispathius pilosus (Granger, 1949), Mimodoryctes proprius Belokobylskij, 2001, M. arabicus Edmardash, Gadallah & Soliman, 2020, Spathius nixoni Belokobylskij & Maetô, 2009, Hecabalodes anthaxiae Wilkinson, 1929, H. radialis Tobias, 1962, H. xylophagi Fischer, 1962, Parallorhogas testaceus (Szépligeti, 1914), Heterospilus (Eoheterospilus) rubrocinctus (Ashmead, 1905), Rhaconotinus menippus (Nixon, 1939), Rhaconotus arabicus Belokobylskij, 2001, Rh. manolus Nixon, 1941, Rh. scirpophagae Wilkinson, 1927 and Rh. sudanensis Wilkinson, 1927.